Peningkatan Kompetensi Guru Sekolah Dasar dalam Pembuatan Asesmen Berdiferensiasi melalui Pelatihan Berbasis Praktik Kolaboratif - Via Yustitia; Danang Prastyo; Achmad Fanani; Rudy Sumiharsono; Vivi Apriani; Putria Putria; Ika Suci Rahayu (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This community service activity was carried out to answer the challenges of modern education, especially in designing assessments that are inclusive and responsive to the diverse learning needs of students. The program involved 25 teachers from five elementary schools in Gunung Anyar Sub-district, Surabaya. The training method includes preparation through a needs survey, exposure to the basic concepts of differentiated assessment, collaborative practice, implementation simulation, and ongoing mentoring. The results of the training showed a significant increase in teacher competence, especially in understanding the concepts of formative, summative, and diagnostic assessments, as well as the ability to design flexible rubrics and assessment formats. As many as 85% of participants understood the objectives of the activity well, 78% felt that they understood the material very well, and 82% felt helped by simulations and hands-on practice. In addition, the training created a culture of productive collaboration between teachers, which was felt by 88% of participants. However, there are challenges in the form of the need for more time for technical deepening of rubric development and implementation assistance in the classroom. Collaborative practice-based training proved effective in improving teachers' competence in differentiated assessment. For the sustainability of the program, further training, the establishment of teacher learning communities and increased school support are recommended. This program is expected to create a more inclusive, innovative and responsive basic education for students' diversity.